Diagenetic controls on reservoir quality of a mixed carbonate-siliciclastic system: Sycamore Formation, Sho-Vel-Tum Field, Oklahoma, USA. (December 2021) - Duarte, David; Milad, Benmadi; Elmore, R. Douglas; Pranter, Matthew J.; Slatt, Roger
Abstract: Reservoir quality (RQ), commonly related to diagenesis, is important to predict formation porosity and permeability. The lack of studies to understand the role of diagenesis on tight reservoirs is a limiting factor for predicting petroleum accumulation in unconventional reservoirs. This study aims to determine the influence of diagenesis on RQ for the mixed carbonate-siliciclastic Sycamore Formation in southern Oklahoma. Additionally, this study assesses other geologic factors such as depositional facies control on diagenesis of the Sycamore. Petrographic observation, geochemical data, and conventional plug analysis from six cores and one outcrop were used to accomplish three objectives: i) reconstruct the paragenetic sequence; ii) determine the role of diagenesis on RQ; and iii) elucidate geological factors that control the diagenetic evolution in the Sycamore strata. Four facies were identified: Massive Calcite-cemented Siltstones, Massive Calcareous Siltstone, Bioturbated Mudstones, and Argillaceous Mudstones. However, this study focuses on the siltstones and their associated diagenetic processes and products. Porosity evolution in the siltstones is affected by cementation and dissolution processes. These diagenetic processes are related to each other; calcite cement decreases permeability during early diagenesis and controls the flow of later diagenetic fluids responsible for feldspar dissolution. Additionally, differences in the supply between a carbonate and siliciclastic material and a change from a carbonate-dominated system to a mixed system through time controls the distribution of calcite cement in the Sycamore. This study allows geologists to understand the diagenetic evolution and to characterize RQ of the Sycamore and similar formations by considering the sediment supply between carbonate- and siliciclastic-dominated systems, changes in stratigraphy, and influx of acidic fluids. Identifying geological controls on diagenesis and defining the influence of diagenesis on RQ in tight formations is important for the exploration and development of unconventional reservoirs, to build predictable porosity and permeability models, and to identify petroleum accumulations. Highlights: Presentation of the diagenetic evolution for the Sycamore Formation in the Ardmore Basin. Cementation and dissolution are the main diagenetic processes that impact reservoir quality of the massive siltstones. Sediment supply between carbonate and siliciclastic systems drives diagenetic processes that affect reservoir quality. Stratigraphic variation of cement between parasequences is linked with conditions during deposition and diagenesis.